Ethnobotanical survey of plants used in the management of obesity in Ibadan, south-western Nigeria (2015)
Background: Until recent times, being obese was considered to be an evidence of wealth in the South-Western part of Nigeria. As a result of a combination of wrong attitudes, ignorance and carefree lifestyle, a sizeable percentage of the population has become predisposed to obesity an emerging problem in developing economies of the world. Objective: To identify and document medicinal plants used in ethno-medical management of obesity in selected rural and urban communities within Ibadan metropolis. This is with the aim of contributing to a database of plants for future systematic biological and chemical evaluation for possible source of anti-obesity agents and drug leads. Materials and methods: An inventory of plant species/natural remedies used in folk medicine to manage obesity in two Local Government Areas of Oyo State was undertaken. Interviews using semi-structured questionnaires and open-ended conversations were conducted among eighty (80) respondents (30% men and 70% women) aged 25 years and above to obtain relevant information.. Results: A total of fifteen (15) plants belonging to twelve (12) genera and twelve (12) families were identified. The usage profiles of the plants were quantified by the quotation frequency/mention index. Respondents from the urban rely more on finished products from local and foreign blends which are mostly multi-component remedies. Conclusion: The study revealed that Ibadan is a rich source of plants indicated in management of obesity. More scientific work especially biological studies are needed to ascertain the efficacy, toxicity, safety and appropriate dosage regimen of these ethno-medicinal remedies.